A method for preparing samarium cobalt magnet
By treating samarium cobalt magnetic powder with hydrogen crushing, ball milling and air flow milling, and combining it with epoxy resin and coupling agent, a more stable samarium cobalt magnet was prepared, which solved the problems of uneven magnetic properties and poor stability of samarium cobalt magnets and achieved the preparation of high-performance magnets.
Patent Information
- Application Number
- CN202510311826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-03-17
AI Technical Summary
Existing samarium cobalt magnets have problems with excessive utilization of rare earth element content and unstable magnetic properties, resulting in uneven magnetic properties and poor stability, making it difficult to meet the needs of high-tech.
By hydrogen crushing and ball milling samarium cobalt magnetic powder with metal elements such as boron, aluminum, tin, zirconium, and iron under hydrogen protection, adding epoxy resin, coupling agent and dispersant, and then forming them under magnetic field and pressure after air flow milling, a more stable samarium cobalt magnet is formed.
The magnetic properties and stability of samarium cobalt magnets are improved, the corrosion resistance of the magnets is enhanced, the production costs are reduced, and it is in line with the concept of sustainable development.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnets, and in particular to a method for preparing a samarium cobalt magnet. Background Art
[0002] Bonded magnets are essential components for modern high-tech products. They are made by mixing permanent magnetic powder with a binder and then molding the magnets through a molding process. Molding methods include injection molding, extrusion molding, and calendaring. They offer advantages such as high shape freedom, high dimensional accuracy, and the elimination of secondary processing.
[0003] CN118574688A discloses a composite material for composite rare earth bonded magnets and a method for composite rare earth bonded magnets. The composite material is prepared by preparing a mixture of magnetic powder, a surfactant, and a binder, and then mixing it with a stearate (ester) and a dispersant. The resulting composite exhibits advantages such as high density and good fluidity. CN115206666A discloses a method for preparing high-density bonded rare earth permanent magnets. The raw material formula is set and the process is followed by crystallization, mixing, pressing, and curing to improve the performance of the bonded rare earth permanent magnets and the utilization rate of the rare earth permanent magnet powder.
[0004] In practical applications, bonded magnets struggle to adapt to the evolving demands of high-tech due to poor composite fluidity and uneven magnet density, which in turn affects magnetic stability. Although coupling agents have been used in samarium-cobalt magnets, several issues remain. Firstly, the rare earth element content leads to overutilization of key rare earth resources, resulting in excessive coercivity and impacting magnetic properties. Secondly, due to limitations in manufacturing technology, the most common method for bonding magnets is to add silane coupling agents, which, combined with non-magnetic binders, can reduce magnet stability. Summary of the Invention
[0005] In view of the market demand for magnet technology, the present invention provides a method for preparing samarium cobalt magnets, which enhances the binding force between the components and improves the stability during subsequent use, and can better meet the current market demand for high-performance magnets.
[0006] The specific technical solutions are as follows:
[0007] A method for preparing a samarium cobalt magnet comprises the following steps:
[0008] S1. Smco magnetic powder, boron, aluminum, cobalt, tin, zirconium, gallium, and iron are subjected to hydrogen crushing treatment under hydrogen protection, and then ball milling treatment is performed at a rotation speed of 200-400 rpm;
[0009] S2. The magnetic powder obtained after ball milling is uniformly mixed with epoxy resin, coupling agent, and dispersant, and then subjected to jet milling at a flow rate of 100-300 m / s for 1-3 h to obtain a mixture;
[0010] S3, place the above mixture in a 2 The mold of the release agent is heated to 100-200°C, and pressed under a magnetic field strength of 1.5-3.0T and a pressure of 150-300MPa for 10-30s to obtain a green body; the green body is kept at 100-150°C for 1-2h under argon atmosphere protection, and cooled to room temperature to obtain a samarium cobalt magnet;
[0011] The amount of each raw material, calculated by weight, includes 200-500 parts of samarium cobalt magnetic powder, 20-40 parts of boron, 0.5-3 parts of aluminum, 0.5-3 parts of tin, 0.5-3 parts of cobalt, 0.5-3 parts of zirconium, 4-10 parts of gallium, 0.5-3 parts of iron, 2-10 parts of epoxy resin, 1-6 parts of coupling agent, and 1-5 parts of dispersant.
[0012] Cobalt: The magnetic moment of cobalt atoms will further interact with the magnetic moments of magnetic elements such as samarium and iron, forming an orderly arrangement, so that the magnet generates a stronger magnetic field, thereby improving the performance of the magnet; it can also inhibit the grain growth and structural changes of the magnet at high temperatures, forming a relatively dense oxide film on the surface of the magnet, preventing external corrosive substances from eroding the internal structure of the magnet, and maintaining the stability of the magnet's performance.
[0013] Zirconium: It helps to form a fine and uniform grain structure, improve the coercive force and remanence of the magnet; it can also improve the thermal stability and anti-aging performance of the magnet, making the performance of the magnet more stable during long-term use.
[0014] Tin: When incorporated into the lattice of samarium cobalt magnets, it causes lattice distortion and affects the distribution of the electron cloud. It also has the ability to deoxidize and desulfurize, and can combine with impurity elements such as oxygen and sulfur contained in metal powder to reduce the segregation of impurities at the grain boundaries, thereby helping to improve the overall performance of the magnet.
[0015] The preparation method of samarium cobalt magnets involves hydrogen crushing treatment, with a hydrogen pressure of 0.1-0.3 MPa, a hydrogen absorption time of 1-3 hours, a vacuum heating temperature of 300-500°C, and a dehydrogenation time of 2-4 hours.
[0016] The method for preparing samarium cobalt magnets involves ball milling, the ball milling medium is zirconia ceramic grinding balls, the processing time is 2-4 hours, and the fine powder particle size is 1-5 μm.
[0017] The coupling agent involved in the preparation method of the samarium cobalt magnet is one or more of a zirconate coupling agent, an aluminate coupling agent, and a titanate coupling agent.
[0018] Preferably, the coupling agent is a mixture of a zirconate coupling agent and a titanate coupling agent.
[0019] The zirconate coupling agent is tetra-n-propyl zirconate.
[0020] The titanate coupling agent is one of isopropyl trioleate acyloxy titanate and bis(dioctyl pyrophosphate acyloxy)ethylene titanate.
[0021] The aluminate coupling agent is distearoyloxyisopropyl aluminate.
[0022] Preferably, the coupling agent involved in the preparation method of the samarium cobalt magnet is a mixture of tetra-n-propyl zirconate and isopropyl trioleate titanate; the specific dosage ratio is 1:1.
[0023] The release agent involved in the preparation method of the samarium cobalt magnet is any one of dimethyl silicone oil and methylphenyl silicone oil.
[0024] The dispersant involved in the preparation method of the samarium cobalt magnet is any one of oleic acid and polyvinyl pyrrolidone.
[0025] The preparation method of the samarium cobalt magnet involves a jet milling process with a processing time of 1-3 hours and a fine powder particle size of 0.5-2 μm.
[0026] The cooling medium involved in the cooling treatment is deionized water or a 15wt% sodium chloride aqueous solution.
[0027] Beneficial effects of the present invention:
[0028] 1. Compared with existing technologies, the combination of samarium cobalt magnetic powder and boron with metal elements such as tin, zirconium, and iron can more effectively enhance the magnetic properties of magnets. Boron refines the grain structure, making it more difficult for magnetic domain walls to move, thereby increasing coercivity. The additional addition of iron and cobalt increases the saturation magnetization and enhances the overall magnetism. Tin, aluminum, and zirconium improve the corrosion resistance of the magnets, effectively preventing performance degradation in high-temperature, humid environments, or environments with the risk of chemical corrosion, thereby reducing maintenance costs and enriching the practical application scenarios of samarium cobalt magnets.
[0029] 2. Compared with the existing technology, the present invention can shorten the distance between various types of micropowders in the magnet by adding epoxy resin, creating conditions for the densification of the magnet; the coupling agent forms a chemical bond between the samarium cobalt magnetic powder and the epoxy resin, enhancing the interfacial bonding force between the two and improving the overall performance and stability of the magnet; the dispersant can improve the fluidity of the composite, reduce the agglomeration of magnetic powder, and improve the uniformity of the magnet density; combined with the release agent, it is beneficial to the flow and molding of the magnetic powder, and can also improve the demolding performance, thereby improving production efficiency and the surface quality of the magnet.
[0030] 3. The multi-component synergistic effect of the samarium cobalt magnet prepared by the present invention optimizes the internal structure of the magnet. The prepared samarium cobalt magnet performs better in structural stability and magnetic properties, and is more likely to exhibit high magnetic properties, thereby reducing production costs, improving economic benefits and resource utilization, and complying with the concept of sustainable development. DETAILED DESCRIPTION
[0031] A method for preparing a samarium cobalt magnet is as follows:
[0032] 200-500 parts by weight of samarium cobalt magnetic powder, 20-40 parts by weight of boron, 0.5-3 parts by weight of aluminum, 0.5-3 parts by weight of tin, 0.5-3 parts by weight of cobalt, 0.5-3 parts by weight of zirconium, 4-10 parts by weight of gallium, 0.5-part by weight of iron are subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.10-0.30 MPa, hydrogen absorption time of 1-3 h, dehydrogenation temperature of 300-500 ° C, and dehydrogenation time of 2-4 h, and then the mixture is subjected to hydrogen crushing treatment in a rotating machine. The ball milling treatment is carried out for 2-4 hours at a speed of 200-400 rpm to obtain magnetic powder with a particle size of 1-5 μm; the magnetic powder obtained after ball milling is evenly mixed with 2-10 parts by weight of epoxy resin, 1-6 parts by weight of coupling agent and 1-5 parts by weight of dispersant, and then the mixture is jet milled for 1-3 hours at a flow rate of 100-300 m / s to obtain a mixture with a particle size of 0.5-2 μm, and then the mixture is placed in a mixture containing 0.1-0.3 g / m 2 The mold containing the release agent is heated to 100-200° C., and the pressure is maintained for 10-30 seconds under the conditions of a magnetic field strength of 1.5-3.0 T and a pressure of 150-300 MPa to obtain a molded green body; the obtained molded green body is kept at 100-150° C. for 1-2 hours under the protection of an argon atmosphere, and cooled to room temperature to obtain a samarium cobalt magnet.
[0033] Epoxy resin: As a binder, it bonds the raw material particles such as samarium cobalt magnetic powder together. The ether bond (COC) and aromatic ring structure in its molecular chain can resist the erosion of chemical media. It further effectively blocks the contact of corrosive media such as chloride ions and sulfate ions with the samarium cobalt magnetic powder inside the magnet, thereby reducing the occurrence of corrosion reactions.
[0034] Coupling agent: It can form chemical bonds between inorganic raw materials such as samarium cobalt magnetic powder and epoxy resin, thereby producing strong physical adsorption, enhancing the interfacial bonding between the two, and improving the overall performance and stability of the magnet.
[0035] Oleic acid: Oleic acid molecules contain unsaturated double bonds and carboxyl groups. Carboxyl groups can chemically adsorb to metal ions on the surface of magnetic powder, preventing magnetic powder from agglomerating with the help of intermolecular forces, thereby improving the compatibility of magnetic powder with binders and enhancing the overall performance of the magnet.
[0036] The parameters and sources of specific chemical substances used are as follows:
[0037] Samarium cobalt magnetic powder: density is 8.3g / cm 3 ; Model: Sm1Co5-24; Hangzhou Kede.
[0038] Tin: Tin granules; Implementation standard: GB / T 728 Q / YXG 002; Specifications: 1-2.5mm; Yunnan Tin Industry.
[0039] Epoxy resin: bisphenol A epoxy resin; Model: EPIKOTE™ 6520-WH-53A; Hexion.
[0040] Tetra-n-propyl zirconate: CAS number: 23519-77-9.
[0041] Bis(dioctylpyrophosphate)ethylene titanate: CAS number: 65467-75-6.
[0042] Distearoyloxyisopropylaluminate: CAS number: 5919-73-3.
[0043] Isopropyl trioleyl titanate: Model: HY-105; CAS No.: 136144-62-2; Hangzhou Jessica Chemical.
[0044] Dimethyl silicone oil: Model: DC-200; Dow Chemical.
[0045] Example 1
[0046] A method for preparing a samarium cobalt magnet is as follows:
[0047] 360g of samarium cobalt magnetic powder, 30g of boron, 1g of aluminum, 1g of tin, 1g of cobalt, 1g of zirconium, 6g of gallium and 1g of iron were subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.20MPa, hydrogen absorption time of 2h, dehydrogenation temperature of 400℃ and dehydrogenation time of 3h, and then ball milled for 3h at a rotation speed of 300rpm to obtain magnetic powder with a particle size of 2μm; the magnetic powder obtained after ball milling was mixed with 6g of bisphenol A epoxy resin, 4g of tetra-n-propyl zirconate and 2g of oleic acid, and then subjected to air flow milling for 2h at a flow rate of 200m / s to obtain a mixture with a particle size of 1μm, and then the mixture was placed in a mixture containing 0.1g / m 2 The mold was filled with dimethyl silicone oil, and the temperature was raised to 120°C. The green body was kept at a magnetic field strength of 2.0T and a pressure of 200MPa for 15s to obtain a green body. The green body was kept at 120°C for 1h under argon atmosphere protection, and cooled to room temperature in a 15wt% sodium chloride aqueous solution to obtain a samarium cobalt magnet.
[0048] Example 2
[0049] A method for preparing a samarium cobalt magnet is as follows:
[0050] 360g of samarium cobalt magnetic powder, 30g of boron, 1g of aluminum, 1g of tin, 1g of cobalt, 1g of zirconium, 6g of gallium and 1g of iron were subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.20MPa, hydrogen absorption time of 2h, dehydrogenation temperature of 400℃ and dehydrogenation time of 3h, and then ball milled for 3h at a rotation speed of 300rpm to obtain magnetic powder with a particle size of 2μm; the magnetic powder obtained after ball milling was mixed with 6g of bisphenol A epoxy resin, 4g of distearoyloxyisopropylaluminate and 2g of oleic acid, and then subjected to air flow milling for 2h at a flow rate of 200m / s to obtain a mixture with a particle size of 1μm, and then the mixture was placed in a mixture containing 0.1g / m 2 The mold was filled with dimethyl silicone oil, and the temperature was raised to 120°C. The green body was kept at a magnetic field strength of 2.0T and a pressure of 200MPa for 15s to obtain a green body. The green body was kept at 120°C for 1h under argon atmosphere protection, and cooled to room temperature in a 15wt% sodium chloride aqueous solution to obtain a samarium cobalt magnet.
[0051] Example 3
[0052] A method for preparing a samarium cobalt magnet is as follows:
[0053] 360g of samarium cobalt magnetic powder, 30g of boron, 1g of aluminum, 1g of tin, 1g of cobalt, 1g of zirconium, 6g of gallium and 1g of iron were subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.20MPa, hydrogen absorption time of 2h, dehydrogenation temperature of 400℃ and dehydrogenation time of 3h, and then ball milled at a rotation speed of 300rpm for 3h to obtain magnetic powder with a particle size of 2μm; the magnetic powder obtained after ball milling was mixed with 6g of bisphenol A epoxy resin, 4g of bis(dioctylpyrophosphate)ethylene titanate and 2g of oleic acid, and then subjected to air flow milling treatment at a flow rate of 200m / s for 2h to obtain a mixture with a particle size of 1μm, and then placed in a mixture containing 0.1g / m 2 The mold was filled with dimethyl silicone oil, and the temperature was raised to 120°C. The green body was kept at a magnetic field strength of 2.0T and a pressure of 200MPa for 15s to obtain a green body. The green body was kept at 120°C for 1h under argon atmosphere protection, and cooled to room temperature in a 15wt% sodium chloride aqueous solution to obtain a samarium cobalt magnet.
[0054] Example 4
[0055] A method for preparing a samarium cobalt magnet is as follows:
[0056] 360g of samarium cobalt magnetic powder, 30g of boron, 1g of aluminum, 1g of tin, 1g of cobalt, 1g of zirconium, 6g of gallium and 1g of iron were subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.20MPa, hydrogen absorption time of 2h, dehydrogenation temperature of 400℃ and dehydrogenation time of 3h, and then ball milled for 3h at a rotation speed of 300rpm to obtain magnetic powder with a particle size of 2μm; the magnetic powder obtained after ball milling was mixed with 6g of bisphenol A epoxy resin, 4g of isopropyl trioleyl titanate and 2g of oleic acid, and then subjected to air flow milling for 2h at a flow rate of 200m / s to obtain a mixture with a particle size of 1μm, and then the mixture was placed in a mixture containing 0.1g / m 2 The mold was filled with dimethyl silicone oil, and the temperature was raised to 120°C. The green body was kept at a magnetic field strength of 2.0T and a pressure of 200MPa for 15s to obtain a green body. The green body was kept at 120°C for 1h under argon atmosphere protection, and cooled to room temperature in a 15wt% sodium chloride aqueous solution to obtain a samarium cobalt magnet.
[0057] Example 5
[0058] A method for preparing a samarium cobalt magnet is as follows:
[0059] 360g of samarium cobalt magnetic powder, 30g of boron, 1g of aluminum, 1g of tin, 1g of cobalt, 1g of zirconium, 6g of gallium and 1g of iron were subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.20MPa, hydrogen absorption time of 2h, dehydrogenation temperature of 400℃ and dehydrogenation time of 3h, and then ball milled for 3h at a rotation speed of 300rpm to obtain magnetic powder with a particle size of 2μm; the magnetic powder obtained after ball milling was mixed with 6g of bisphenol A type epoxy resin, 2g of isopropyl trioleyl titanate, 2g of tetra-n-propyl zirconate and 2g of oleic acid, and then subjected to air flow milling for 2h at a flow rate of 200m / s to obtain a mixture with a particle size of 1μm, and then the mixture was placed in a medium containing 0.1g / m 2 The mold was filled with dimethyl silicone oil, and the temperature was raised to 120°C. The green body was kept at a magnetic field strength of 2.0T and a pressure of 200MPa for 15s to obtain a green body. The green body was kept at 120°C for 1h under argon atmosphere protection, and cooled to room temperature in a 15wt% sodium chloride aqueous solution to obtain a samarium cobalt magnet.
[0060] Comparative Example 1
[0061] A method for preparing a samarium cobalt magnet is as follows:
[0062] 360g of samarium cobalt magnetic powder, 30g of boron, 1g of aluminum, 1g of tin, 1g of cobalt, 1g of zirconium, 6g of gallium and 1g of iron were subjected to hydrogen crushing treatment under the conditions of hydrogen absorption pressure of 0.20MPa, hydrogen absorption time of 2h, dehydrogenation temperature of 400℃ and dehydrogenation time of 3h, and then ball milled for 3h at a speed of 300rpm to obtain magnetic powder with a particle size of 2μm; the magnetic powder obtained after ball milling was evenly mixed with 2g of oleic acid and then jet milled for 2h at a flow rate of 200m / s to obtain a mixture with a particle size of 1μm, and then the mixture was placed in a mixture containing 0.1g / m 2 The mold was filled with dimethyl silicone oil, and the temperature was raised to 120°C. The green body was kept at a magnetic field strength of 2.0T and a pressure of 200MPa for 15s to obtain a green body. The green body was kept at 120°C for 1h under argon atmosphere protection, and cooled to room temperature in a 15wt% sodium chloride aqueous solution to obtain a samarium cobalt magnet.
[0063] Test Example 1
[0064] Magnetic declination test
[0065] The magnetic declination of samarium cobalt magnets prepared in Examples 1-5 and Comparative Example 1 was tested according to the method for measuring the magnetic declination of permanent magnets in GB / T 43266-2023. The power switch of the three-channel flux integrator was turned on to preheat the flux integrator for more than 15 minutes. The measurement range was ±5mWb, and the drift of the flux integrator should be less than 0.001mWb within 5 seconds. The interference magnetic field, the distance between the ferromagnetic object and the movement of the ferromagnetic object should all comply with GB / T38437. The interference magnetic field strength should be less than 0.01T, the distance between the ferromagnetic object and the sample should be greater than 50cm, and the ferromagnetic object should remain stationary during the test. The results are shown in Table 1.
[0066] Table 1 Magnetic declination results
[0067] Magnetic declination / ° Example 1 1.04 Example 2 1.15 Example 3 1.12 Example 4 1.08 Example 5 0.81 Comparative Example 1 1.28
[0068] Compared with Comparative Example 1, the magnetic deflection angles of Examples 1-5 were lower. This may be because the coupling agent enhanced the bonding between the magnetic powder and the epoxy resin, stabilized the internal structure of the magnet, reduced magnetic domain disorder, and thus reduced the magnetic deflection angle. The addition of distearoyloxyisopropylaluminate in Example 2 enhanced interfacial bonding and improved dispersibility of the magnetic powder in the epoxy resin.
[0069] In contrast, Example 1 adds tetra-n-propyl zirconate, one end of which reacts with metal ions on the magnetic powder surface to form a chemical bond, while the other end interacts with the epoxy resin. This structure tightly connects the magnetic powder to the resin, reducing internal stress concentration and thus lowering magnetic deflection. Example 4 adds isopropyl trioleyl titanate, a unique structure that forms a stable connection between the magnetic powder and the resin, optimizing the internal structure of the magnet and reducing magnetic deflection.
[0070] Example 5: Isopropyl trioleyl titanate and tetra-n-propyl zirconate are compounded to improve the dispersion of magnetic powder in the matrix. The molecular structures and properties of tetra-n-propyl zirconate and isopropyl trioleyl titanate complement each other, enabling a more uniform distribution of magnetic powder in the matrix and preventing agglomeration. Once the magnetic powder is evenly dispersed, the magnetic field distribution within the magnet becomes more uniform, reducing the impact of local magnetic field inhomogeneities on magnetic declination and improving magnet stability.
[0071] Test Example 2
[0072] Coercivity test
[0073] The samples prepared in Examples 1-5 and Comparative Example 1 were cut into rectangular parallelepipeds with a regular shape, 1 cm in length, 0.5 cm in width, and 0.5 cm in height, conforming to the measurement requirements of an ATM-4 magnetic property tester. The samples were placed in a 1.5 T magnetic field (typically twice the expected coercivity), and the reverse magnetic field was gradually applied, with the coercivity values recorded. The results are shown in Table 2.
[0074] Table 2 Coercivity results
[0075] Magnetic induction intensity / T Coercive force value / kA / m Example 1 1.534 723 Example 2 1.522 788 Example 3 1.518 751 Example 4 1.517 704 Example 5 1.558 652 Comparative Example 1 1.505 829
[0076] Compared to Comparative Example 1, the samarium cobalt magnetic powder and other inorganic materials in Examples 1-4 form strong physical adsorption with the added epoxy resin, enhancing the interfacial bonding between the two, reducing the surface energy between the magnetic powder particles, and reducing particle agglomeration. This allows for a more uniform dispersion of the magnetic powder in the organic matrix, thereby improving magnetic induction intensity and coercivity. The bis(dioctyl pyrophosphate)ethylene titanate added in Example 3 is highly acidic. The strong acidity of the pyrophosphate group may result in a stronger acid-base reaction with the metal oxide on the surface of the samarium cobalt magnetic powder, potentially leading to excessive surface reaction and reagglomeration of the magnetic powder during pressing, affecting the magnet density and orientation. The use of isopropyl trioleyl titanate in Example 4 may be more conducive to promoting the formation of a fine, uniform, and well-oriented grain structure in the magnet, hindering the movement of magnetic domain walls and making the magnet more stable during magnetization and demagnetization, thereby improving coercivity.
[0077] Furthermore, in Example 5, isopropyl trioleyl titanate can improve the interfacial bonding between the magnetic powder and the organic matrix, enhancing the mechanical properties and structural stability of the magnet; tetra-n-propyl zirconate has advantages in optimizing the surface properties of the magnetic powder and promoting the dispersion of the magnetic powder. When used in combination, the dispersion of the magnetic powder in the organic matrix can be made more uniform, the magnetic field distribution more uniform, and the magnetic induction intensity is improved. At the same time, isopropyl trioleyl titanate and tetra-n-propyl zirconate can improve the interfacial bonding and microstructure, enhance the magnet's ability to resist external interference, and make the coercive force value more stable; this helps to maintain the integrity of the magnet structure when the samarium cobalt magnet is affected by external forces, temperature changes, and other factors during subsequent use, thereby improving the stability of the magnet.
[0078] Test Example 3
[0079] Corrosion resistance test
[0080] The samarium-cobalt magnets prepared in Examples 1-5 and the comparative example were sprayed with a 5% sodium chloride solution and a 2% sulfuric acid solution, respectively, for accelerated corrosion. The ambient temperature was set at 60±5°C, the spraying time was 10 minutes, the rest time was 4 hours, and the test period was 120 hours. After corrosion treatment, the magnets were rinsed with 1000 mL of water, dried with hot air at 35°C, and cooled to room temperature. The roughness of the coatings before and after corrosion was measured using an SPMI-200D roughness profiler, and the roughness change rate of the coatings after corrosion was calculated. The weight change rate of the coatings after corrosion was also calculated by weighing. The specific test data are shown in Table 3.
[0081] Table 3 Corrosion resistance test results
[0082]
[0083] Compared to Comparative Example 1, the coupling agent added in Examples 1-5 forms a chemical bond or strong physical adsorption between the inorganic samarium cobalt magnetic powder and the organic epoxy resin, enhancing the interfacial bonding between the two and making the magnet structure more compact. This effectively blocks ions in the corrosive solution from penetrating into the magnet, reducing the contact area between the magnet and the corrosive medium, thereby reducing the degree of corrosion. Methyl silicone oil, which acts as a lubricant between the magnetic powder particles and between the magnetic powder and the mold, helps form a more uniform structure during the magnet molding process, reduces stress concentration points within the magnet, and avoids accelerated corrosion caused by stress concentration.
[0084] The addition of tetra-n-propyl zirconate in Example 1 forms a stable chemical structure at the interface between the magnetic powder and the epoxy resin, effectively preventing the diffusion of ions and slowing down the corrosion rate. The chemical properties of the zirconium element are relatively stable, and it may participate in the formation of a surface film with corrosion resistance to a certain extent, further improving the corrosion resistance. In Example 4, isopropyl trioleyl acyloxy titanate has the ability to form special chemical bonds with the surface containing samarium cobalt magnetic powder, forming a more uniform and denser magnet structure, thereby promoting the dispersion and anchoring of the magnetic powder in the epoxy resin. In particular, the acyloxy group it contains may react chemically with corrosive substances, consume some corrosive ions, and form a protective reaction product layer on the magnet surface, thereby improving the magnet's tolerance to chloride ions, hydrogen ions, and sulfate ions.
[0085] Example 5 The siloxy groups contained in isopropyl trioleyl titanate and tetra-n-propyl zirconate can react with the hydroxyl groups on the surface of the magnetic powder after hydrolysis. At the same time, the monoalkoxy groups in the titanate molecules and the alkoxy groups in the zirconate interact with the epoxy resin, enhancing the stability of the interface and reducing the penetration path of corrosive substances. Furthermore, the synergistic effect of the two can make the magnetic powder more evenly dispersed in the matrix, the resulting magnet structure is more dense, the internal pores and defects are reduced, the channels for corrosive substances to penetrate are reduced, and the corrosion resistance of the magnet is thereby improved. In subsequent practical applications, the doubly reinforced interface can more effectively block the intrusion of corrosive substances, and even in long-term corrosive environments, the integrity of the magnet structure can be maintained, thereby improving the corrosion resistance of the magnet.
Claims
1. A method for preparing a samarium cobalt magnet, characterized in that: The following steps are involved: S1. Smco magnetic powder, boron, aluminum, cobalt, tin, zirconium, gallium, and iron are subjected to hydrogen crushing treatment and then ball milled at a rotation speed of 200-400 rpm; S2. The magnetic powder obtained after ball milling is mixed evenly with epoxy resin, coupling agent and dispersant, and then subjected to jet milling at a flow rate of 100-300 m / s; S3, placing the mixture after the jet milling treatment in a mold containing a release agent, heating it to 100-200° C., and pressing it under a magnetic field strength of 1.5-3.0T and a pressure of 150-300 MPa for 10-30 seconds to obtain a molded green body; keeping the temperature at 100-150° C. for 1-2 hours under an argon atmosphere, and cooling it to room temperature to obtain a samarium cobalt magnet; The amount of each raw material, calculated by weight, includes 200-500 parts of samarium cobalt magnetic powder, 20-40 parts of boron, 0.5-3 parts of aluminum, 0.5-3 parts of tin, 0.5-3 parts of cobalt, 0.5-3 parts of zirconium, 4-10 parts of gallium, 0.5-3 parts of iron, 2-10 parts of epoxy resin, 1-6 parts of coupling agent, and 1-5 parts of dispersant.
2. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The hydrogen pressure of hydrogen crushing treatment is 0.1-0.3MPa, the hydrogen absorption time is 1-3h, the vacuum heating temperature is 300-500℃, and the dehydrogenation time is 2-4h.
3. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The ball milling medium is zirconia ceramic grinding balls, the processing time is 2-4 hours, and the fine powder particle size is 1-5 μm.
4. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The coupling agent is one or more of a zirconate coupling agent, an aluminate coupling agent, and a titanate coupling agent.
5. The method for preparing a samarium cobalt magnet according to claim 4, wherein: The zirconate coupling agent is tetra-n-propyl zirconate; the titanate coupling agent is one of isopropyl trioleate acyloxy titanate and bis(dioctyl pyrophosphate acyloxy)ethylene titanate.
6. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The jet mill treatment time is 1-3 hours, and the fine powder particle size is 0.5-2 μm.
7. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The release agent is any one of dimethyl silicone oil and methylphenyl silicone oil.
8. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The dispersant is any one of oleic acid and polyvinyl pyrrolidone.
9. The method for preparing a samarium cobalt magnet according to claim 1, wherein: The cooling medium involved in the cooling treatment is deionized water or a 15wt% sodium chloride aqueous solution.
10. A samarium cobalt magnet, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
High-density bonded rare earth permanent magnet and preparation method thereof
CN115206666A
Preparation method of sintered samarium-cobalt magnet
CN109706338A
Heavy rare earth element-free low-coercivity temperature coefficient high-temperature samarium-cobalt permanent magnet material and preparation method thereof
CN111370191A